(untitled) (TEL Tempo, Espaço e Linguagem, 2023)
The article intends to map the presence and participation of women in the public debate about heritage in Brazil at the moment of its constitution and institutionalization. It takes as research objects and sources the Revista do Patrimônio, a journal linked to SPHAN/DPHAN and the main medium for discussion and propagation on heritage issues in Brazil, and the Revista de História e Arte, an important vehicle for criticism of the heritage policies implemented by the federal preservation agency. Some considerations on the relations between women’s history and the heritage debate are made, using some resources from intellectual history and the history of intellectuals.